Human dental pulp stem cells: A sanctuary for relapsing Bartonella quintana. (April 2021) - Oumarou Hama, Hamadou; Hamada, Attoumani; Aboudharam, Gérard; Ghigo, Éric; Drancourt, Michel
Abstract: Bartonella quintana is a facultative intracellular bacterium responsible for relapsing fever, an example of non-sterilizing immunity. The cellular sanctuary of B. quintana in-between febrile relapses remains unknown but repeated detection of B. quintana in dental pulp specimens suggested long-term half-life dental pulp stem cells (DPSCs) as candidates. As the capacity of DPSCs to internalize microscopic particles was unknown, we confirmed that DPSCs internalized B. quintana bacteria: Gimenez staining and fluorescence microscopy localized B. quintana bacteria inside DPSCs and this internalization did not affect the cellular multiplication of DPSCs during a one-month follow-up despite the increase in the bacterial load. B. quintana -infected DPSCs did not produce Tumor Necrosis Factor-α whereas an important production of Monocytes Chemoattractant Protein-1 was observed. These unprecedented observations suggest the possibility that DPSCs are shelters for the long-term persistence of B. quintana in the host, warranting further experimental and clinical investigations. Highlights: Bartonella quintana is responsible for considerable fatal infections in humans. DPSCs are mesenchymal stem cells with tissue regeneration capacity. Highlights B. quintana as a paradigmal organism.